Estimation of IL-17A and IFN-y in the Burn of Patients that Afflicted by Different Bacterial Types - A. Risan, Farhan; Kh. Salih, Mahmmod; A. Salih, Taher (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study was to detect the level of IL-17A and IFN-y in the burn patients that were afflicted by different types of bacteria compared with the control group of patients that were not afflicted by bacteria. The sample collection was carried out from 15/10/2017 to 22/1/2018 at the burns hospital in Baghdad. Samples were collected from patients sera. Collection samples were from 88 burn patients, 58 of whom were infected by different types of bacteria; 29 patients were males, and 29 patients were females. The other 30 patients that were not infected by bacteria were 15 males and 15 females; this group was used as a control group. The investigation of the level of IL-17A and IFN-y was carried out by ELISA assay in the teaching laboratories in Baghdad. The results showed a decrease in the level of IL-17A in the patients, which was 43.43 pg + 5.426 compared to the control group, which was 55.77 pg + 5.418. And it showed a decrease in IFN-y levels of patients was 36.95 pg + 5.808 compared to the control group, which was 46.63 pg + 5.816. The current study reported a highly significant difference in IL-17A and IFN-y levels between the patients and the control group at the level (P < 0.01).